The ABC Of HCVs - Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma (Federación Nacional de Cultivadores de Palma de Aceite, 2020)
The Biodiverse Oil Palm Landscape project (PPB in Spanish) was executed between 2012 and 2018 by the National Federation of Oil Palm Growers (FEDEPALMA in Spanish), in association with Cenipalma, the Humboldt Institute and WWF Colombia. It was financed by the Global Environment Facility (GEF) and its implementing agency was the Inter-American Development Bank (IDB).
Keywords: Agroindustria; Biodiversidad; Aceite de palma; Producción; Sostenibilidad